The Possibility of Applying Quality Management System ISO9001: 2008 in Station Project Al Rustumiya - A Case Study - هاشم, صبيحة قاسم; طه, قيس قاسم (Journal of Economics and Administrative Sciences, 2017)
The research study of the possibility of the application of the quality management system under the international standard ISO ISO9001: 2008 in the station project Rustumiya wastewater treatment of the Department of SEWER BAGHDAD - Baghdad MOREALITY as the first step in the right direction towards the implementation of total quality management (TQM), and the research Find the gap between the international standard and the quality system used in the organization surveyed through the use of checklists to analyze the gap, the checklist have included (191) items distributed on five basic requirements, according to the appearance in the international standard, namely, (quality management system, management responsibility, resource management, product realization, measurement, analysis and improvement), and after the diagnosis of the gap the search using some means of quality control statistically as PARETO DIAGRAM and CAUSE-EFFECT DIAGRAM for the purpose of analysis that gap and identify the strengths and weaknesses of the organization and the priorities to be followed by the TOP management in the organization in order to bridge the gap and including contributes to absorb and adopt the TOP management of the specification as Standard international, for the rehabilitation of the organization in the direction of obtaining a certificate of conformity to ISO ISO9001: 2008, the most important findings of research is a gap between the requirements of international standard and the reality of the application and documentation actual in the surveyed organization, which was increased by 52.7% due to partial application and the weak to the requirements specification in addition to documenting it partial, as well as the search Aograe some exceptions in the requirements of international standard and exclusively in the requirements of sub contained in item No. (7) of the International Standard ISO ISO 9001:2008, for the reason of the nature of the work of the organization and the type of products, the  exception was in the following sub-requirements (3-7: Design and development ,2-5-7: validating processes for production and service delivery, 3-5-7:IDENTIFICATION AND TRACEABILITY, 4-5-7 :   customer property,  5-5-7: reservation of  product), these exceptions have been made under item (1-2: Application) of international standard.